Analysis of Public Policy Implementation on Population Information Digitalization at The North Bekasi District Office - Sugeng, Willy Gunardi; Subagja, Iwan Kurniawan; Hakim, Azis (Dinasti Publisher, 2025)
The purpose of this study is to analyze the implementation of population information digitalization at the North Bekasi District Office. This study is a qualitative study with structured interviews with 5 informants. The results of the research that has been conducted show that: (1) The implementation of the population information digitalization policy in North Bekasi District still faces obstacles in the implementation of SIAK, such as low competence of service officers, infrastructure that does not meet specifications, unstable internet networks, and socialization and counseling that are not carried out continuously, making the community not understand the procedures that must be carried out in processing population documents. (2) Factors that influence the implementation of the population information digitalization policy in North Bekasi District, include: support, capacity, and value. (3) Strategies that need to be implemented by the apparatus in North Bekasi District in determining the success or failure of implementing the information digitalization policy in their area include: the need to implement minimum service standards as a reference in the performance of the administration of the population administration sector in order to improve the quality of services to the public, the need for improvements in the management of administrative services in North Bekasi District, the need to improve facilities and infrastructure supporting public services, and the need to add service officers, both honorary and contract, and the budget for implementing activities needs to be increased in order to anticipate the increasing number of people using services.